Environmental Seasonality Regulates Community Evenness in Neotropical Bat Communities - Estrada-Villegas, Sergio; Pérez-Torres, Jairo; McGill, Brian J.; Stevens, Richard D. (Frontiers in Ecology and Evolution, 2022)
Evenness is a key community property that provides insights into resource acquisition and ecosystem functioning. However, it is unclear how other community properties influence evenness after integrating the effect of environmental gradients. Using 61 neotropical bat communities, we tested the hypothesis that evenness increases in communities that have low species richness and low biomass because the negative effect of richness and biomass on evenness is regulated by environmental seasonality. We selected among path models to determine how temperature seasonality, the most important gradient across study sites, affected richness and biomass as drivers of evenness. Employing three indices of evenness, we found that more seasonal climate reduces species richness, and lower richness increases evenness. Moreover, a decline in biomass with increasing seasonality also increases evenness. A decrease in resource specialization and rarity as sites become more seasonal may explain the negative relationship between seasonality, richness and evenness. Moreover, the negative effect of biomass on richness and evenness may be due to an expansion of niche space and a positive effect of smaller body size on diversification rates, which may allow more species packing and greater richness. We believe our results bring us closer to a unified theory of which factors control evenness in a community.